La estimulación temprana y su incidencia en el desarrollo psicomotriz de los niños y niñas de primer grado de la unidad educativa fiscomisional “Santa Mariana de Jesús, del cantón Saraguro. Período lectivo 2014 – 2015”. Lineamientos alternativos - Guamán Fárez, Mónica Abigail (2015)
This research work entitled: EARLY STIMULATION AND ITS IMPACT ON PSYCHOMOTOR DEVELOPMENT OF CHILDREN OF SCHOOL, FIRST DEGREE GENERAL EDUCATION BASIC SCHOOL TEACHING APPLICATION OF “SANTA MARIANA DE JESÚS” “CANTON SARAGURO THE PERIOD 2014-2015.” This investigation has the general objective: To determine whether early stimulation affects the psychomotor development of high school children, first grade general education basic school isped implementation “Santa Mariana de Jesús "in the city of Saraguro, period 2014-2015. The methods and techniques that were used for data collection and analysis were: the scientific method, deductive, inductive, synthetic, and the same statistical model that served to expose, represent the relationship and importance of early stimulation management in developing psychomotor. As techniques were applied: the survey of teachers to identify early stimulation activities engaged in daily work day, and Ozeretzky test in order to evaluate the psychomotor development of High School children, Unidad Education degree from the school of application “Santa Mariana de Jesús “. From the survey of teachers and with reference to question 3 indicate the activities you performed for early learning children. the 29 % of the teachers surveyed early stimulation engaged in as: game, children's literature and techniques graph plastic, and, 14% puppet. Early stimulation of children high school girls, first grade general education basic. In applying Ozeretzky test, 72% of children obtained a psychomotor skill satisfactory and unsatisfactory 28%, so it is concluded that there is a high percentage of children in school, first grade general basic education where there is good psychomotor development. All these experiences that adapt driving children at these ages, guarantee better integrated development it will help in school readiness.